2020
DOI: 10.1101/2020.04.07.029033
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcription-coupled repair inDrosophila melanogasteris independent of the mismatch repair pathway

Abstract: 1Transcription-coupled repair (TCR) removes base damage on the transcribed strand of a gene to 2 ensure a quick resumption of transcription. Based on the absence of key enzymes for TCR and 3 empirical evidence, TCR was thought to be missing in Drosophila melanogaster. The recent 4 demonstration of TCR in S2 cells raises the question about the involved genes. Since the 5 mismatch repair (MMR) pathway serves a central role in TCR, at least in Escherichia coli, we 6 studied the mutational signatures in flies with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 54 publications
2
5
0
Order By: Relevance
“…Deviations from strand symmetry in the 5LR could not be associated with selection-driven processes, either at the mono- or oligonucleotide level. The observed slight, constant deviations along the region possibly reflect the effect of transcription-coupled repair leading to mutational asymmetries (transcription-associated mutation bias-TAMB), in line with the recent studies (Bergman et al, 2017; Deger et al, 2019; Törmä et al, 2020). Furthermore, deviations in the biallelic frequency spectra of the 5LR were more compatible with the neutral process, GC -biased gene conversion, rather than directional selection.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Deviations from strand symmetry in the 5LR could not be associated with selection-driven processes, either at the mono- or oligonucleotide level. The observed slight, constant deviations along the region possibly reflect the effect of transcription-coupled repair leading to mutational asymmetries (transcription-associated mutation bias-TAMB), in line with the recent studies (Bergman et al, 2017; Deger et al, 2019; Törmä et al, 2020). Furthermore, deviations in the biallelic frequency spectra of the 5LR were more compatible with the neutral process, GC -biased gene conversion, rather than directional selection.…”
Section: Resultssupporting
confidence: 89%
“…It seems that the base composition and higher-order oligonucleotide motifs in the 5LR of short introns of Drosophila can be used as a neutral reference. Recent studies showed that Drosophila performs transcription-coupled repair (Deger et al, 2019; Törmä et al, 2020) and this might also lead to deviation from strand symmetry in the 5LR (Bergman et al, 2017). Yet it can be assumed that this effect would be similar along the intron, and as long as selection is absent in the 5’ region, it could be used to control and quantify the effects of splicing-coupled selection in other parts of the intron.…”
Section: Introductionmentioning
confidence: 99%
“…We used mutations generated in (36) to perform a direct estimation of mutation rates. The VCF file for the DGRP Freeze 2.0 calls (46) was downloaded from: http://dgrp2.gnets.ncsu.edu/data.html in October 2019.…”
Section: Methodsmentioning
confidence: 99%
“…The VCF file for the DGRP Freeze 2.0 calls (46) was downloaded from: http://dgrp2.gnets.ncsu.edu/data.html in October 2019. We used the GATK tool CallableLoci (52) (version 4.0.12.0) to calculate the number of callable sites for each of the 7 lines from the same BAM files that were used in (36). We estimated the SNVs - using all SNVs and separated for A/T and G/C pairs - and indel mutation rates with the following formula: m /( t × c ) where m is the total number of mutations across the 7 lines, t is equal to 10 generations, c is the total number of callable sites over each line.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation